Effect of idiopathic pulmonary fibrosis on postoperative prognosis of patients with non-small cell lung cancer - Na LI; Xiaoli LI; Jing LI; Jinye WANG (Zhongguo Linchuang Yixue)
ObjectiveTo investigate the effect of idiopathic pulmonary fibrosis (IPF) on the prognosis of patients with non-small cell lung cancer ( NSCLC ). MethodsA total of 98 patients with NSCLC who underwent radical surgery in Honghui Hospital, Xi’an Jiaotong University from March 2018 to March 2019 were selected, and were divided into the IPF group and the non-IPF group. The clinicpathological and surgical data were compared between the two groups. The follow-up time was up to March 31, 2024. The endpoint event was NSCLC-related death or NSCLC recurrence, and the death and recurrence during the follow-up period were recorded. Kaplan-Meier survival curve and log-rank test were used to compare survival rate between the two groups. Cox regression analysis was used to analyze the related factors affecting postoperative death and NSCLC recurrence. ResultsOf the 98 patients included, 45 (45.92%) had IPF. Compared with the non-IPF group, the patients were older, proportion of female patients and preoperative serum C-reactive protein (CRP) level were higher, and the preoperative serum albumin level was lower in the IPF group (P＜0.05). The median follow-up time was 3.7（0.7, 5.6）years. The 1-, 3-, 5-year overall survival rates and recurrence-free survival rates of patients in the IPF group were shorter than those in the non-IPF group (P＜0.05). Cox regression analysis showed that high-degree differentiation and IPF were risk factors for survival of NSCLC patients (P＜0.05), and vascular infiltration, bigger tumor and IPF were risk factors resulting in NSCLC recurrence (P＜0.05). Conclusions For NSCLC patients, IPF can significantly shorten the overall survival and recurrence-free survival, and is a common risk factor resulting in postoperative death and recurrence.